Tuntutan Pekerjaan, Intensi Keluar Kerja, dan Peran Burnout sebagai Mediator - Roswani, Julia; Zamralita; Idulfilastri, Rita Markus; Roebianto, Adiyo (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
The Covid-19 pandemic is a very critical period and has become an epidemic that has spread throughout the world, thus affecting all aspects of people's lives in the world. The increasing demand related to information technology automation since the Covid-19 pandemic has been followed by increasing job demands for employees in the information technology industry. In line with increasing job demands, the phenomenon of burnout and turnover intention is faced by company X. High job demands can cause fatigue and can influence employees to leave the organization or company. There is a relationship between job demands and turnover intention, but this relationship is not strong (weak) so a burnout mediator role is needed. The purpose of this research is to look at the role of burnout as a mediator in the relationship between job demands and turnover intention. Turnover intention is a deliberate action with full awareness to leave the organization. Job demands are the physical, psychological, social and organizational aspects related to work that are needed to support both physical and psychological demands that are associated with physical and psychological harm. Burnout is a symptom of emotional exhaustion and a negative view (cynicism) of what one does. The number of samples in this study was 71 people. The sampling technique is non-probability sampling with convenience sampling. Measuring the variable of turnover intention uses a measuring tool, measuring burnout using the burnout assessment tool, measuring job demands using the job demands-resources questionnaire. The results of this research are that there is a relationship between job demands and burnout. There is a role of burnout as a mediator in the relationship between job demands and intention to leave work.